2022
DOI: 10.3389/fmolb.2022.944955
|View full text |Cite
|
Sign up to set email alerts
|

Protein of a thousand faces: The tumor-suppressive and oncogenic responses of p53

Abstract: The p53 protein is a pleiotropic regulator working as a tumor suppressor and as an oncogene. Depending on the cellular insult and the mutational status, p53 may trigger opposing activities such as cell death or survival, senescence and cell cycle arrest or proliferative signals, antioxidant or prooxidant activation, glycolysis, or oxidative phosphorylation, among others. By augmenting or repressing specific target genes or directly interacting with cellular partners, p53 accomplishes a particular set of activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 311 publications
(409 reference statements)
0
12
0
Order By: Relevance
“…p53 is a transcriptional factor and protector of the genome, preventing cells from undergoing malignance transformation. In the context of tumor-suppressive activities, p53 has a growing list of functionalities that goes beyond triggering apoptosis, senescence, and cell cycle arrest . The problem arises when destabilized p53 mutations hijack its tumor suppressor activities, and p53 malignancy occurs.…”
Section: Phase Separation and Transition Of The P53 Tumor Suppressor ...mentioning
confidence: 99%
See 2 more Smart Citations
“…p53 is a transcriptional factor and protector of the genome, preventing cells from undergoing malignance transformation. In the context of tumor-suppressive activities, p53 has a growing list of functionalities that goes beyond triggering apoptosis, senescence, and cell cycle arrest . The problem arises when destabilized p53 mutations hijack its tumor suppressor activities, and p53 malignancy occurs.…”
Section: Phase Separation and Transition Of The P53 Tumor Suppressor ...mentioning
confidence: 99%
“…For example, phosphorylation of FUS and TDP-43 leads to LLPS inhibition, , whereas in Tau, it is a PS inducer . The N-terminal and C-terminal flexible regions of p53 are often termed “molecular antennas”, as these segments are targets of several PTMs, but to date, there are no reports linking p53 PTMs as regulators of LLPS formation or dissolution.…”
Section: Modulators Of Phase Separation and Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one study has shown that, in estrogen-positive breast cancer cells, the expression of a truncated p53 mutant increased BCL-2, thus decreasing their apoptosis in breast cancer cells [ 409 ]. Moreover, evidence has suggested that certain gain-of-function or loss-of-function mutations of the TP53 gene, as found in many cancers, turn p53 into an oncogene [ 410 ]. In this context, it should be considered that TP53 mutations are very common in hepatocellular carcinoma, and their interplay in the regulation of apoptosis and autophagy has not been investigated [ 411 ].…”
Section: Interplay Between Apoptosis and Autophagymentioning
confidence: 99%
“…P53 also functions as a protein modulator. During ischemia-related oxidative stress, P53 accumulates in the mitochondrial matrix through its interaction with cyclophilin D, leading to the opening of the permeability transition pore and, ultimately, necrosis [ 8 , 9 ]. P53 also binds to glucose-6-phosphate dehydrogenase (G6PD), the rate-limiting enzyme of the pentose phosphate shunt and decreases flux [ 10 ].…”
Section: Introductionmentioning
confidence: 99%